2016
DOI: 10.1039/c6an00582a
|View full text |Cite
|
Sign up to set email alerts
|

A ratiometric solvent polarity sensing Schiff base molecule for estimating the interfacial polarity of versatile amphiphilic self-assemblies

Abstract: A newly synthesised Schiff base molecule (PMP) existing in equilibrium between non-ionic and zwitterionic forms displays solvent polarity induced ratiometric interconversion from one form to another, such novelty being useful to detect the medium polarity. The specific interface localisation of PMP in versatile amphiphilic self-assembled systems has been exploited to monitor their interfacial polarity by evaluating such interconversion equilibrium with simple UV-Vis spectroscopy. In spite of the large differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Tahara and co-workers have established a heterodyne-detected electronic sum frequency generation (HD-ESFG) spectroscopic method to estimate the self-assembled system-induced acid/base p K a shift and have monitored the interfacial pH values. , It has been identified that the interfacial pH is substantially altered from the bulk pH. Recently, we have introduced a new interfacial pH/polarity monitoring method for biologically important micelles and vesicles by utilizing interface-interacting pH/polarity-detecting probes. The estimated values of the pH/polarity differences between the bulk phase and the interface are observed to be similar to that obtained from the HD-ESFG method. Most importantly, the inherent simplicity of our detection technique can be highly effective for monitoring the shape- and structure-dependent manipulation of the pH/polarity at the complex biological membrane interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Tahara and co-workers have established a heterodyne-detected electronic sum frequency generation (HD-ESFG) spectroscopic method to estimate the self-assembled system-induced acid/base p K a shift and have monitored the interfacial pH values. , It has been identified that the interfacial pH is substantially altered from the bulk pH. Recently, we have introduced a new interfacial pH/polarity monitoring method for biologically important micelles and vesicles by utilizing interface-interacting pH/polarity-detecting probes. The estimated values of the pH/polarity differences between the bulk phase and the interface are observed to be similar to that obtained from the HD-ESFG method. Most importantly, the inherent simplicity of our detection technique can be highly effective for monitoring the shape- and structure-dependent manipulation of the pH/polarity at the complex biological membrane interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…S13†). 29 The dielectric constant of the buffer solution was adjusted to 44–45 with addition of 58% (w/w) ethanol at pH 2.0–6.5,30 where the δ value was estimated to be ∼0.7 (Fig. 2C and D, gray and black curves).…”
Section: Resultsmentioning
confidence: 99%
“…A spiro-rhodamine-glucose molecule (RHG)45 and a Schiff-base molecule (PMP)46 were prepared according to earlier procedures. Briefly, spiro-rhodamine 6G hydrazide was prepared by the reaction of rhodamine 6G hydrochloride with hydrazine in ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where log k, p refer to the analyte retention factor, the compound polarity, respectively. (log k) 0 and are the constants related to the stationary phase, is the polarity of mobile phase [27,28,30].…”
Section: Calculation Of the Polarity Of Target Compoundsmentioning
confidence: 99%